Humble Leadership Benefits Employee Job Performance: The Role of Supervisor–Subordinate Guanxi and Perceived Leader Integrity - Yang, Bin; Shen, Yimo; Ma, Chenlu (Frontiers in Psychology, 2022)
Humble leadership has been spotlighted in leadership scholarship for its effectiveness in many positive outcomes, especially when compared with leader narcissism and arrogance. However, we still have limited knowledge about how humble leadership casts influences on important outcomes and the boundary conditions of the effect of humble leadership is understudied. Drawing from social exchange theory, we elaborate on how humble leadership is positively related with employee job performance via the effect of supervisor-subordinate guanxi. Further, based on attribution theory, we predict that perceived leader integrity will moderate the relationship between humble leadership and supervisor-subordinate guanxi and the indirect relationship between humble leadership and employee job performance. Results from 304 valid supervisor-employee paired surveys support our moderated mediation model. We found that supervisor-subordinate guanxi mediated the relationship between humble leadership and job performance; the interaction between humble leadership and perceived leader integrity predicted supervisor-subordinate guanxi; and perceived leader integrity moderated the indirect effect from humble leadership to job performance through supervisor-subordinate guanxi. Theoretical and practical implications, as well as limitations and future directions are discussed.